Dermoscopy of Psoriasis: A Cross Sectional Study - Thapa, Deeptara Pathak; Adhikari, Harihar; Bhandari, Sajana (Nepal Journal of Dermatology, Venereology & Leprology, 2022)
Introduction: Dermoscopy is a non-invasive tool that aids in the diagnosis of dermatological diseases. Objectives: The study aims to evaluate the dermoscopic features of psoriasis in the skin. Materials and Methods: All patients clinically diagnosed with psoriasis were enrolled in the study. Dermoscopic findings were studied using a handheld pocket dermoscope (Dermlite DL1) with high magnification. Dermoscopic examination used both polarizing and non-polarizing lenses. Results: The age of the patients ranged from 12 years to 58 years, and the mean age of presentation was 30 years (+/-12.7 years). There were 52% females and 48% males. In dermoscopy, vascular changes were seen in 90%. Vessel arrangement was seen as uniform in 80% of the cases and non-uniform in 20%. Dotted vessels were seen in 88%, glomerular and comma-shaped vessels in 2%. In 94%, white scales were seen, followed by yellow scales in 2% and mixed types in 4%. The background color was red in 68% of cases, pink in 26%, and brownish in 6%. Pigmentary changes were observed in 16%. Follicular changes were observed in 6%. Conclusion: The present study analyzed the characteristic of dermoscopic features in psoriasis. Further studies should be conducted, including inflammatory disorders and their correlation with dermoscopic features.